Sintesis Katalis Basa Na2SiO3/Fe3O4 Untuk Reaksi Transesterifikasi Waste Cooking Oil (WCO) Menjadi Biodiesel - Tarsensius Wabady Happy Limbong; Edy Saputra; Khairat Khairat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
This research aims to derive biodiesel from waste cooking oil (WCO) through transesterification using heterogeneous base catalyst Na2SiO3/Fe3O4. Catalyst Na2SiO3/Fe3O4 was synthesized from fly ash palm oil, sodium hydroxide, and iron powder. Tranesterification operated under reaction temperature is 60°C (±2) for 2 hours, with stirring 300 rpm. The highest yield of biodiesel is 95.83% under the transesterification methanol/WCO molar ratio 1:10, loading catalyst 3%-w. Density (40°C) of biodiesel is 886.85 kg/m3, kinematic viscosity (40°C) is 5.87 mm2/s, flash point is 204°C, acid value is 0.74 mg-KOH/g-biodiesel, and water content is 0.36%.Keyword: Biodiesel, Esterification, Catalyst, Transesterification, WCO.